Contribuição da densidade do PSA para predizer o câncer da próstata em pacientes com valores de PSA entre 2,6 e 10,0 ng/ml - Castro, Hugo Alexandre Sócrates de [UNIFESP] (2010)
Objective: To study the profile of patients with PSA values between 2.6 and 10.0 ng/ml who underwent prostate biopsy at São Paulo Hospital, a university Hospital from the Federal University of São Paulo, determining possible patterns that might lead to a reduction of unnecessary biopsies. Methods: We performed a cross-sectional study with patients with PSA values between 2.6 and 10.0 ng/mL who were refered to the Interventional Radiology Service for prostate biopsies between 2007 and 2009. One thowsand two hundred and eighty two were included in this study. Results: Of the 1282 patients undergoing prostate biopsy, the prevalence of cancer was 28.6% (336 patients). Patients with positive biopsies were older, with values of PSA and PSA density higher than patients com negative biopsies. Neoplasia tends to be more common in the peripheral region of the gland compared to the transition zone. There was no difference between the tumor distribution and the Gleasson scale. Regarding PSA density (PSAD), patients with cancer had an average of 0.31 ng/ml/cc compared with 0.10 ng/ml / cc in patients with negative results (p<0,001). Recent data propose a PSAD cutoff value of 0.15 ng/ml/cc. Using this cutoff, we found a specificity of 74% and sensitivity of 70%. When we used a cutoff value of 0.09 ng/ml/cc, we obtained a sensitivity of 84% (95% CI: 80-87%) and specificity of 75% (95% CI: 72-78%) and area under the ROC curve of 0.794 .The likelihood ratio for the two cutoffs chosen. We find the criterion for 0.15 ng/ml/cc value for RV + and RV - = 2.72 = 0.41. As for the criterion 0.09 ng/ml/cc, we find a value of RV + and RV - = 3.36 = 0.21. Conclusion: In this study we showed that the systematic use of PSA density in patients with PSA values between 2.6 and 10.0 ng/mL patients can substantially reduce the amount of unnecessary procedures.